Oculang: Empowering Communication through Blink Language Detection - S., Suriya; S., Anubharathi V; G., Bharathi; R., Harshada; R., Vignesh Aditya; G., Sundarsree B (IRO Journal on Sustainable Wireless Systems, 2025)
Oculang is a communication system that uses computer vision and machine learning techniques to enable individuals with neurodegenerative disorders to communicate using eye gestures. The application focuses on detecting facial landmarks, gaze estimation, and blink detection to analyze combinations of eye movements captured from video input and produce message outputs. Dlib’s shape predictor (68 facial landmarks) and OpenCV-based image processing methods are used to extract and process the features of the eye region. A decision-making algorithm maps the detected gestures and predefined keywords for message generation. The application supports both real-time video capturing and uploading video through a Django-based user interface. Experimental evaluation on recorded datasets of eye movements demonstrated robust performance in accurately recognizing blinks, winks, and gaze directions, validating the system’s reliability.
Keywords: Computer Vision; Human-Computer Interaction; Assistive Technology; Accessibility; Vision-Based Interaction; Facial Landmark Detection; Gaze Estimation; Thresholding Techniques; Geometric Ratios